Development of algorithms for improving the accuracy and performance speed of a functional analogtodigital converter - Mychuda, Lesya (Eastern-European Journal of Enterprise Technologies, 2018)
This paper presents results of the study into the functional analog-to-digital conversion with a replaceable logarithm base. In known analog-to-digital converters, an increase in speed leads to a decrease in accuracy and vice versa. In contrast to the known methods, the method developed makes it possible to improve conversion rate without increasing errors. It was implemented in circuits with switched capacitors since it is the use of the phenomenon of redistribution and accumulation of charge in capacitor cells that makes it possible to create converters with a variable logarithm base. Another advantage of such implementation consists in reliability, low power consumption and high manufacturability. This enables integration of the converters with a variable logarithm base into various automation devices, e.g. both in blocks of evaluators of stationary information and computing systems and miniature or mobile sensors of the object state. In the course of the study, three algorithms of replacing the logarithm base with a ratio of capacitances have been developed. The conversion step height depends on the logarithm base and varies in each conversion sub-band. Descending sweep takes place in downward steps. It is suitable for large input signals. Ascending sweep in upward steps is better for small input values. Two-sided sweep is universal. The conducted study had allowed us to estimate errors and conversion time of the proposed device. An optimal number (10) of steps – apportionings in each sub-band and an optimal number (4) of conversion sub-bands have been chosen. An error less than 0.005 % was obtained for these values during conversion time of 100 μs (40 clock cycles). The results obtained make it possible to manufacture analog-to-digital functional converters with increased accuracy and speed, applicable for various industrial and scientific tasks. A special feature is the possibility of user's choice of the required accuracy and speed, even before the start of conversion.